My grandfather's song - Phung, Nguyen Quang; Huynh, Kim Lien (Make Me a World, 2023)
A picture book about a family's connection to their land, their home, and each other. Long ago, Grandfather came to a new land. Fish swam in the water, birds chirped in the sky, monkeys played in the trees. And in this wilderness, with his own two hands, Grandfather built a house. It wasn't easy. But the land gave him what he needed. And it became his home. Decades later, his grandson will have all he needs: a head full of memories, two capable hands, and the heart to appreciate family, nature, and home.